2011
DOI: 10.1016/j.crohns.2010.11.006
|View full text |Cite
|
Sign up to set email alerts
|

3g mesalazine granules are superior to 9mg budesonide for achieving remission in active ulcerative colitis: A double-blind, double-dummy, randomised trial

Abstract: Once-daily 3g mesalazine administered as granules is superior to 9mg budesonide OD administered as capsules for achieving remission in mild-to-moderately active UC. However, it is noteworthy that remission of UC was attained in about 40% of budesonide-treated patients with a rapid onset of resolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 41 publications
0
47
1
1
Order By: Relevance
“…The absolute clinical and endoscopic remission rates seen in this study are lower than the remission rates reported in several recent UC trials 2 9 11. There are a number of potential reasons for these differences, which relate primarily to the study endpoints and inclusion/evaluation criteria used.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…The absolute clinical and endoscopic remission rates seen in this study are lower than the remission rates reported in several recent UC trials 2 9 11. There are a number of potential reasons for these differences, which relate primarily to the study endpoints and inclusion/evaluation criteria used.…”
Section: Discussioncontrasting
confidence: 63%
“…Additionally, endoscopic improvements, particularly mucosal healing, may be an important indicator of longer-term outcomes, such as the likelihood of colectomy over the following year 22. In their study comparing Budenofalk with Salofalk, Gross et al 9 defined remission as a Rachmilewitz CAI score of ≤4, which might mean anything up to a score of 2 for stool frequency (defined as 30–60 bowel actions/week) and 2 for rectal bleeding (defined as a little blood). The mesalazine MMX studies2 11 12 used similar UCDAI criteria to our study, but employed a less thorough method (flexible sigmoidoscopy) for endoscopic evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…This is contrary to the results from the earlier trial by Gross et al , which compared the efficacy of (PH-dependent release) budesonide (9mg/day) to oral mesalamine (3g/day) and concluded that budesonide is inferior to mesalamine. 39 The two studies used different primary outcome (clinical remission in Gross et al study vs. combined endoscopic and clinical remission in CORE I) and different mesalamine dosages (3 g vs 2.4g), both factors and the different budesonide formulations may have contributed to the inconsistent results. Furthermore, the CORE I trial was not sufficiently powered to detect differences between the active compactor groups.…”
Section: Clinical Efficacymentioning
confidence: 99%
“…10,11 Therefore, an ideal colon-specific delivery system for UC therapeutics should prevent premature drug release before reaching the colon and deliver sufficient amounts of the drug to the inflamed area of the distal colon. Fine tuning of the formulation may be necessary to account for longer transit times in the gut, as well as slightly higher pH values (around 7.3) in the distal small intestine.…”
Section: Introductionmentioning
confidence: 99%